Certainty of justice : reform in the crime victim movement - Weed, Frank J., 1942- (New York : Aldine de Gruyfer, 1995)
Since the late 1970s, the movement portrayed in this volume has been demanding that the law stand in for society as a whole, and use its authority to demonstrate the triumph of good over evil rather than simply to bear out the bureaucratic process. In so doing, its proponents are changing our concept of justice by defining a role for crime victims beyond the evidentiary need of the prosecution in a court of law.
1. Reform Politics for Crime Victims: Government, Grass Roots, and Grievance -- 2. The Vilification of the Crime Problem -- 3. National Umbrella Organizations: Issue Prominence and Influence -- 4. Programming for Political Pulse -- 5. Community-Based Victim Service and Advocacy Organizations -- 6. Victim Rights and the Symbolism of Reform -- 7. Conclusion -- Appendix: Case Study and National Survey Method and Material.
Includes bibliographical references and index.
Keywords: Victims of crimes -- Services for -- United States; Victims of crimes -- Legal status, laws, etc. -- United States; Social movements -- United States; Social advocacy -- United States